2016
DOI: 10.1111/1462-2920.13398
|View full text |Cite
|
Sign up to set email alerts
|

Physiological adjustments and transcriptome reprogramming are involved in the acclimation to salinity gradients in diatoms

Abstract: Salinity regimes in estuaries and coastal areas vary with river discharge patterns, seawater evaporation, the morphology of the coastal waterways and the dynamics of marine water mixing. Therefore, microalgae have to respond to salinity variations at time scales ranging from daily to annual cycles. Microalgae may also have to adapt to physical alterations that induce the loss of connectivity between habitats and the enclosure of bodies of water. Here, we integrated physiological assays and measurements of morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 119 publications
(144 reference statements)
1
30
1
Order By: Relevance
“…Changes in cellular Chla concentrations and photosystem proteins in response to nutrient status, but independent of oxidative stress, will result in a re-organisation of PSII, and therefore a change in F v /F m (Butler, 1978;Hailemichael et al, 2016). The small, but significant, changes in F v /F m in our experiments (D F v / F m = c. 0.05) (Figs 4b, S2) were most likely to be a signature of PSII re-organisation, not of ROS damage, with the exception of the significant F v /F m decrease in T. oceanica under hypersaline conditions (DF v /F m = 0.2) which may reflect oxidative stress (Jahnke & White, 2003;Bussard et al, 2017). Therefore, we conclude that the strong correlation between intracellular DMSP and F v /F m in T. oceanica is not due to ROS damage, but rather an indirect co-occurring response to the environmental change.…”
Section: Researchmentioning
confidence: 73%
See 1 more Smart Citation
“…Changes in cellular Chla concentrations and photosystem proteins in response to nutrient status, but independent of oxidative stress, will result in a re-organisation of PSII, and therefore a change in F v /F m (Butler, 1978;Hailemichael et al, 2016). The small, but significant, changes in F v /F m in our experiments (D F v / F m = c. 0.05) (Figs 4b, S2) were most likely to be a signature of PSII re-organisation, not of ROS damage, with the exception of the significant F v /F m decrease in T. oceanica under hypersaline conditions (DF v /F m = 0.2) which may reflect oxidative stress (Jahnke & White, 2003;Bussard et al, 2017). Therefore, we conclude that the strong correlation between intracellular DMSP and F v /F m in T. oceanica is not due to ROS damage, but rather an indirect co-occurring response to the environmental change.…”
Section: Researchmentioning
confidence: 73%
“…By contrast, growth at temperatures above T opt and under nutrient limitation (steadyor nonsteady-state) was linked to metabolic imbalances, in which photosynthesis and respiration are decoupled (Hockin et al, 2012;Baker et al, 2016;Wordenweber et al, 2018). The metabolic conditions of marine phytoplankton resulting from steady-state hyper-and hyposaline stresses are relatively unknown, as most previous studies have focused on euryhaline species or nonsteady-state responses to osmotic shock (Qasim et al, 1972;Macler, 1988;Jahnke & White, 2003;Bussard et al, 2017). Extreme salinity stress is however well known to induce oxidative stress (Jahnke & White, 2003;Acosta-Motos et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Under stressful conditions, the enhanced production of EPS is usually accompanied with increased transcript levels of genes related to carbon metabolism. Bussard et al (2017) found an up-regulation of the genes related to carbon concentrating mechanisms (CCMs) in the model diatom T. weissflogii in response to lower salinities down to 20. Decreased temperature and increased salinity induced a significant up-regulation of the genes involved in carbohydrate metabolism of the ice diatom F. cylindrus in order to protect themselves from the stress caused by the freezing condition (Aslam et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…energy production [ 79 ]) were not reduced in early phases, when cells up-regulated genes for RNA processing and metabolic activity to maintain growth. The diatom Thalassiosira weissflogii also alters its transcriptome to maintain rates of carbon metabolism and growth between salinities of 21 to 35 [ 85 ], and increased EPS production in response to salinity occurs in Phaeodactylum tricornutum and Cylindrotheca closterium [ 35 , 86 ]; F. cylindrus [ 36 ]; and to a variable extent in T. weissflogii [ 85 ]. In phase IV (−4 °C, 52 salinity), F. cylindrus maintained its growth, with the main EPS production pathway up-regulated and various Man, Glc and uronic acid-rich EPS being produced.…”
Section: Discussionmentioning
confidence: 99%